2022
DOI: 10.1177/09637214211062876
|View full text |Cite
|
Sign up to set email alerts
|

Insights Into Human and Nonhuman Primate Handedness From Measuring Both Hands

Abstract: Handedness is part of our everyday lives, but where does it come from? Researchers studying nonhuman primates and young children have approached this question from different perspectives—evolutionary and developmental, respectively. Their work converges on the conclusion that measurement matters in the science of handedness. Coming to a consensus on assessment will guide future research into the origins of handedness. A candidate behavior for promoting multidisciplinary comparison is role-differentiated bimanu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 41 publications
(56 reference statements)
1
9
0
Order By: Relevance
“…One of the most robust behavioral indicators of hemispheric specialization in humans, as well as in nonhuman primates (see the recent review by Nelson, 2022) and other species (Rogers et al, 2013), is handedness (i.e., side preference for the right or the left hand) (Ocklenburg and Güntürkün, 2018). The human population presents approximately 90% right-handers while left-handers constitute approximately 10% (Papadatou-Pastou et al, 2020; but see Faurie et al, 2005, who found 26.9% of left-handers among the Eipo in Papua New Guinea).…”
Section: Human Handednessmentioning
confidence: 99%
“…One of the most robust behavioral indicators of hemispheric specialization in humans, as well as in nonhuman primates (see the recent review by Nelson, 2022) and other species (Rogers et al, 2013), is handedness (i.e., side preference for the right or the left hand) (Ocklenburg and Güntürkün, 2018). The human population presents approximately 90% right-handers while left-handers constitute approximately 10% (Papadatou-Pastou et al, 2020; but see Faurie et al, 2005, who found 26.9% of left-handers among the Eipo in Papua New Guinea).…”
Section: Human Handednessmentioning
confidence: 99%
“…Contrary to human research, infants are poorly represented in the primate handedness literature. Most studies of primate handedness, like research in primate cognition more broadly, have used adult samples (Nelson, 2022 ; Nelson et al, 2022 ). Far fewer still are infant primate handedness studies that have measured multiple behaviors at multiple timepoints—prerequisites for testing predictive links in a developmental cascade.…”
Section: Point Of View: Scant Attention Has Been Paid To Testing Deve...mentioning
confidence: 99%
“…The lack of a head-hand link for reaching may be due to when reaching data were collected. Reaching is now regarded as a poor measure of hand preference outside of infancy (for a discussion, see Nelson, 2022 ). Furthermore, the presence of a head-hand link for bimanual manipulation requires further investigation to uncover the potential mechanism.…”
Section: Point Of View: Scant Attention Has Been Paid To Testing Deve...mentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned previously, it would be necessary to assess whether differences in anatomy, behavioral ecology, sociality or cognitive capacities may produce different selective pressures on the evolution of manual laterality in primates. Also, another potential factor necessary for inclusion in future studies and meta-analyses is rearing history and developmental context (Nelson, 2022). Contradictory results have been reported on this issue.…”
Section: Potential Moderator Variablesmentioning
confidence: 99%